Between Conservatism and Progressivism: The Young Penghulu in East Java's Legal Paradigm Addresses Disability Issues in Marriage - Nur Hadi, Mukhammad; Ali Sabri, Fahruddin; Masum, Ahmad (Hukum Keluarga Islam IAIN LANGSA, 2023)
The legal knowledge of penghulu on disability issues determines how to implement laws that advocate for persons with disabilities. This paper traces the legal paradigm of seven Penghulus in East Java who were newly inducted in 2022 against several articles in the Compilation of Islamic Law (KHI) that touch on disability issues. Some of the themes tracked are marriage guardians (article 22), marriage witnesses (article 25), and polygamy (article 57). It is an empirical study using conceptual and philosophical approaches. This article finds that most young East Javanese penghulu still need an advocate interpretation paradigm because they read the articles authentically and grammatically, not sociologically or teleologically. The benefit (maslahah) aspect of these articles is also considered to look more authentic. Therefore, the argument of advocates for the rights of persons with a human rights perspective is not widely involved. As a result, persons with disabilities who are guardians of marriage, witnesses of marriage, and wives can become victims of neglect of fundamental civil rights in marriage. It is where the conservative paradigm of the young penghulu comes into being strong and dominant. The existence of the progressive paradigm is also buried and framed in the current conservative paradigm. This finding is certainly an important note about how the government indirectly shapes the contestation of conservative and progressive paradigms in family law.